Investigation Into the Early Childhood Care and Education Centre-Based Active Learning Curriculum Approach: Teachers’ Concerns at Four ECCE Centres in the St. George East Educational District - Paul-Wiseman, Maria (My University, 2014)
This study investigated four teachers’ concerns about the early childhood care and education (ECCE) centre-based active learning curriculum approach at four government ECCE centres in the St. George East Educational District in Trinidad and Tobago. Data were collected through interviews. The findings revealed that the teachers had intense concerns related to informational, personal, management, and collaboration stages, but minimal concerns were reported at the awareness, consequence, and refocusing stages. Emerging concerns were related to ineffective training and understanding, time demands, availability of resources, inadequate staff, and lack of support from the cluster administrator.
Keywords: Concerns; Case studies; Early childhood care and education; Teacher attitudes; Curriculum implementation; Preprimary teachers; Teaching techniques; Trinidad and Tobago